Argentina : Capital Market Financing for Infrastructure - World Bank Group (World Bank, Washington, DC, 2017)
Argentina’s improved sovereign credit rating has helped to spur the recent sub-sovereign and corporate bond issues. In early April 2016, Standard & Poor’s upgraded Argentina’s sovereign ratings for local and foreign currency debt to B from B-. This follows the ratings upgrade from Moody’s which raised Argentina’s sovereign rating for foreign currency denominated debt from C1 to B3 in 2016. This rating was re-affirmed by Moody’s in March 2017. Since Argentina’s re-entry into the international capital markets in early 2016, there has been USD 8.4 billion and USD 4.4 billion of bonds issued by sub-sovereign and corporate entities which is being used, in part, being used to support infrastructure projects. Although investor appetite has been relatively strong, it is difficult to ascertain the level of liquidity for sub-sovereign debt over the long-term. The potential level of involvement of foreign and local banks in the financing of infrastructure is still to be determined once Public-Private Partnerships (PPP) projects are tendered. Going forward, the issues that will impact the participation of lenders are: (i) the timing for completing and implementing the underlying regulatory framework for PPPs; (ii) the development of a project pipeline and subsequent tenders; (ii) macroeconomic conditions. The ability of the renewable energy projects under the RenovAR program to obtain bank financing will serve as useful benchmark for the rest of the PPP program. Although the enactment of the capital markets law is intended to reduce market inefficiencies, additional legislation, regulation and policies are needed to deepen and widen local capital markets. This law, which is still under legislative review, may not go far enough to develop the institutional investor base needed to provide long-term financing for infrastructure. Provisions could be added or new legislation could be developed which will: (a) encourage insurance companies to offer new types of products; (b) rebuild private pension systems by incentivizing the establishment of asset management companies; (c) providing preferential tax treatment for closed end mutual funds or value capture adjacent to real estate; (d) supporting the establishment of REITs; (e) reviewing the governance structure, mission, and investment strategy of the FGS; (f) support the development of long-term hedging instruments to manage currency risk through trusts or related mechanisms; and (g) promote the issuance of peso-linked bonds while developing a peso/dollar hedge market.